The analyze of the marketing mix towards consumer's decisionin using freight forwarding services at PT. JNE Pekanbaru - Maya Regina; Sri Restuti; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims are to analyze the influence of marketing mix i.e. product, price, promotion, place, people, process and service towards the customer’s decicion making both simultanously and partially at PT JNE Pekanbaru. The population is the customer of PT JNE Pekanbaru. The number of samples are 125 respondent by using Hair model with Accidental Technique Sampling. Data analysis method used quantitative method by using SPSS version 17.0.According to the research, by using the simultant test (F-test) showed that all of the independent variables have a positive influence to the customer’s decision, while using partially test (t-test) showed thas product, place, people, process ande service have a positive and significant influence to the customer’s decision meanwhile price and promotion have no significant influence. Based on the research determinant correlation (R2) of the independent variable are about 50,7 %, and the rest of it ± 49,3 persen are influenced by other variables that not included in this research.Keyword: Product, Price, Promotion, Place, People, Process, Customer Service, Marketing Mix. and Customer Decision Making